Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/antiox9040290
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Inflammation as Targets for Novel Preventive and Therapeutic Approches in Non Communicable Diseases

Abstract: As recently reported by the World Health Organization (WHO), Non-Communicable Diseases (NCDs) has been rising over the last century representing the main cause of death and disability for the general population regardless of age, region, or gender [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Many phytochemicals are currently being studied for their potential benefits against the major threats to human health, i.e., non-communicable diseases including cardiovascular disorders, cancer, autoimmunity, neurodegenerative diseases, as well as metabolic impairments related to insulin resistance and liver disorders, such as nonalcoholic fatty liver disease (NAFLD). Oxidative stress and reactive oxygen species (ROS) overproduction are considered as common denominators of such a variety of pathologies; hence, in a preventive and therapeutic perspective, many efforts are being made to discover and characterize the antioxidant properties of natural compounds [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many phytochemicals are currently being studied for their potential benefits against the major threats to human health, i.e., non-communicable diseases including cardiovascular disorders, cancer, autoimmunity, neurodegenerative diseases, as well as metabolic impairments related to insulin resistance and liver disorders, such as nonalcoholic fatty liver disease (NAFLD). Oxidative stress and reactive oxygen species (ROS) overproduction are considered as common denominators of such a variety of pathologies; hence, in a preventive and therapeutic perspective, many efforts are being made to discover and characterize the antioxidant properties of natural compounds [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation, oxidative stress, and dysregulated autophagy are common features in noncommunicable diseases and may be key targets for the development of novel therapeutic strategies [ 43 ]. Previous studies have shown that GMP exerts immunomodulatory, anti-oxidative, and anti-inflammatory activities in rodent models of noncommunicable diseases in which macrophage activation is related with pathophysiology [ 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays oxidative stress is also the main target for the development of new prevention and therapeutic strategies for NCDs (5). Under normal conditions, the increased free radicals can be controlled by the body's various antioxidant defenses.…”
Section: Introductionmentioning
confidence: 99%